Burnout In Orthopaedic and Trauma Surgeons of Nepal - Maharjan, Dipendra; Sinha, Ritesh; Shah, Rajesh Pratap; Magar, Shusil Rana (Journal of Karnali Academy of Health Sciences, 2020)
Background: Burnout is a syndrome, which consists of detachment from patients and colleagues, emotional tiredness and lack of achievements in personal life. Freudenberger HJ coined the term “burnout” in the 1970s and categorized into three categories namely depersonalization, emotional exhaustion, and personal achievement. Since then there has been a lot of research on the effects of stress, work or emotion, on behavior and in professional life. Surgeons are particularly exposed to burnout and more common than in the general population and have been found that burnout in the orthopaedic surgeon is more than in any other specialty. There is a high level of dissatisfaction in orthopedic surgeons in Nepal, who are emotionally harassed and tired of lack of achievements. There was research on burnout and over orthopedic surgeons in different countries but there was no research on burnout and no studies were conducted in orthopedic surgeons of Nepal. Therefore, this study was conducted to evaluate the burnout level of orthopaedic surgeons in Nepal. Methods: An observational transverse contacted survey among Nepalese orthopaedic and trauma surgeons by voluntary sample technique was conducted in Kathmandu Nepal between September 2018 - August 2019; using a self-administered questionnaire in digital as well as the printed form that was based on the Maslach Burnout Inventory. Demographic and occupational data were also collected. Results: Out of all contacted surgeons, 34 responded. The mean age was 35 and all were male. Almost everyone showed a high level of emotional exhaustion (94%), depersonalization (100%) and only 32% showed a high level of personal achievement. Conclusion: Burnout syndrome is consisting of depersonalization, emotional exhaustion, and personal achievements and showed a frightening level of emotional exhaustion, depersonalization and a satisfactory level of personal achievements.